KESESUAIAN Durio zibethinus Murr. DAN Nephelium lappaceum L. PADA LAHAN BLOK PEMANFAATAN TAHURA GUNUNG MENUMBING, BANGKA BARAT Suitability of Durio zibethinus Murr. and Nephelium lappaceum L. on the Utilization Block at Menumbing Mountain Grand Forest - Nuri Nursjahbani; Omo Rusdiana; Darmawan . (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2018)
The conversion of forests to non-forests by communities has resulted in the loss of forest ecosystems and a reductionin the area of land that can be utilized for nature tourism at Menumbing Mountain Grand Forest Park (MMGFP).Revegetation is needed by planting several types of forest vegetation that generate economic benefits for the communityas well as attracting natural tourism in MMGFP utilization block such as durian (Durio zibethinus Murr.) and rambutan(Nephelium lappaceum L.). It is necessary to evaluate utilization block to ensure that both species grow well andproductivity of fruits have optimal yield. This study aims to obtain recommendations for improvements of the land qualityalong with the suitable characteristics to be limiting the growth of durian and rambutan. Suitability evaluation of durianand rambutan refers to the land suitability classification criteria compiled by Indonesian Center for Agricultural LandResources Research and Development by matching the growth requirements of both types with land utilization blockcharacteristics. Durian and rambutan are considered to be marginally suitable (S3) for planting in most land utilizationblock. The limiting factor of durian and rambutan is rooting medium, i.e texture and nutrient retention, comprising pH ororganic carbon (C-organic). The texture of the soil can not be modified because it is permanent. Soil pH can beincreased through liming. The soil C-organic content can be increased through the application of organic fertilizer. Afterboth efforts are made, the planted durian and rambutan are likely to grow well and productivity of the fruit will beoptimal so that revegetation in the utilization block will be successful and problems faced in MMGFP will be solved.Key words: Liming, marginally suitable, organic fertilizer, revegetation